2017
DOI: 10.1016/j.scib.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

WB crystals with oxidized surface as counter electrode in dye-sensitized solar cells

Abstract: Tungsten boride (WB) crystals, whose surface tends to be oxidized when exposed to air, were demonstrated to have a comparable activity to platinum as counter electrode material in dye-sensitized solar cells (DSSCs). The synergistic effect of both catalytically active surface layer WO x and electronically conductive internal WB is considered to be responsible for the high activity of the WB crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The reader can obtain more information about the phosphides CE catalysts in previous review paper [18] . Commercial micro-sized tungsten boride (WB) was used as CE for DSCs which showed a PCE of 7.07%, close to that using Pt CE (7.75%) [99] . The superior catalytic activity of WB stemmed from the excellent catalytic activity of nonstoichiometric WO x surface layer and high conductivity of internal WB for electron transfer.…”
Section: Phosphides Borides Silicides and Telluridesmentioning
confidence: 81%
“…The reader can obtain more information about the phosphides CE catalysts in previous review paper [18] . Commercial micro-sized tungsten boride (WB) was used as CE for DSCs which showed a PCE of 7.07%, close to that using Pt CE (7.75%) [99] . The superior catalytic activity of WB stemmed from the excellent catalytic activity of nonstoichiometric WO x surface layer and high conductivity of internal WB for electron transfer.…”
Section: Phosphides Borides Silicides and Telluridesmentioning
confidence: 81%
“…Figure e,f shows the XPS spectra of the C1s region. The experimental curve for the investigated materials can be deconvoluted into six separate components, indicating the presence of the following bonds: W–C, B–C, C–C, C–OH, O–C–O, and O–CO with binding energy in the intervals 282.33–283.11, 284.20–284.26, 284.82–285.02, 285.54–286.21, 286.79–287.65, and 288.33–289.46 eV, respectively. ,, There are no significant differences in C 1s XPS spectra of samples containing either WB 5– x –WB 2 or WB and WB 2 ; see Figures e,f and S9 in the Supporting Information. The main contribution corresponding to the C–C bond comes from the graphite structure of the carbon shell of each formed agglomerate and the carbon bound to oxygen (see Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…The B 1s spectra for WB 5– x –WB 2 (50/50%) and WB 5– x –WB 2 (67/33%) were deconvoluted into four and five components, namely, with BE­(B 1s) in the interval 183.92–184.61 eV indicating the presence of a B–B bond of amorphous boron; with BE­(B1s) in the interval 187.08–187.62 indicating the presence of a W–B bond; with BE­(B1s) in the intervals 189.19–189.46 and 190.51–191.11 eV indicating B–O bonds in B x O y (see Figure c,d and Table S5), , as well as for the sample of WB 5– x –WB 2 (67/33%), it was additionally identified the B 1s state with BE in the interval 185.01–186.06 eV related to the B–C bond; see Figure d and Table S5 in the Supporting Information. It should be noted that, as in the case of tungsten, the presence of the B–O bond indicates a partial oxidation of the sample surface by atmospheric oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…As for W 2 B 5 , the W 4f peaks assignments belong to the W-B and W-O bond, and the peaks of B 1s are attributed to the B-O, B-W, B-B bond. [41,42] The formation of the W-O and B-O bond is due to the adsorbed oxygen in the air. [42] In contrast, Ar-annealed W 2 B 5 /Li precursor shows all the peaks corresponding to W 2 B 5 , except that a B-Li bond peak at 185.9 eV is observed (Figure 2f), [43] which confirms the Li entering into the W 2 B 5 lattice and explains the difference in growth efficiency between W 2 B 5 and W 2 B 5 /Li compound.…”
Section: Resultsmentioning
confidence: 99%
“…[41,42] The formation of the W-O and B-O bond is due to the adsorbed oxygen in the air. [42] In contrast, Ar-annealed W 2 B 5 /Li precursor shows all the peaks corresponding to W 2 B 5 , except that a B-Li bond peak at 185.9 eV is observed (Figure 2f), [43] which confirms the Li entering into the W 2 B 5 lattice and explains the difference in growth efficiency between W 2 B 5 and W 2 B 5 /Li compound. In addition, a comparison between two samples found that the peaks of the Ar-annealed W 2 B 5 /Li shifted to lower energy, which was due to the lower electronegativity of Li than that of W and B.…”
Section: Resultsmentioning
confidence: 99%